Postawy europejskich konsumentów wobec produktów tradycyjnych i regionalnych - Borowska, Agnieszka (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2008)
The article attempts to present situation and consumer’s opinion about traditional and regional food market in Poland. It describes past and future potential threats resulting from the initial phase of creation of niche food alimentation market in Poland. The article presents fragmentary results of research conducted within a grant-research project implemented with the financial support of Foundation Cooperation Fund, Agro-Smak 2 Programme concerning the opinions of consumers and their attitudes, i.e. inclinations to purchase traditional/regional products in Poland. The research was conducted with the technical help of PENTOR Research International S.A. This review was prepared based on the primary empirical material collected during two rounds of research – round 1 conducted between September 20–25, 2007 (research stage 1) and between October 4–9, 2007 (research stage 2). The research was based on a representative sample of 1028 and 1032 Polish nationals of at least 15 years of age. The researchers re159 lied on Omnibus type of research using direct interview technique (face-to-face interviews at respondents’ homes) aided by state-of-the art recording and data processing technique – computer record. The aim of the research was to determine the respondents’ level of declarative knowledge of Polish traditional/regional food products and to define a potential group of purchasers of these products, as well as to find out whether the products, which apply for official EU registration, are purchased by consumers, at least from time to time. Questions were grouped in thematic groups. The goal was to collect feedback from respondents concerning their awareness and frequency of purchase of traditional/regional food products as chosen from among the range of different products of the same category available in the market. The questionnaire was also expected to reveal the respondents’ determination to purchase the products in question in the future as well as to unveil possible assumptions behind not purchasing the products concerned and behind the consumers’ attempts to seek for information on the products under analysis.